Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1095/biolreprod.114.118570
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Microenvironment Dictates Androgen Production by Murine Fetal Leydig Cells in Primary Culture1

Abstract: Despite the fact that fetal Leydig cells are recognized as the primary source of androgens in male embryos, the mechanisms by which steroidogenesis occurs within the developing testis remain unclear. A genetic approach was used to visualize and isolate fetal Leydig cells from remaining cells within developing mouse testes. Cyp11a1-Cre mice were bred to mT/mG dual reporter mice to target membrane-tagged enhanced green fluorescent protein (GFP) within steroidogenic cells, whereas other cells expressed membrane-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 64 publications
(82 reference statements)
0
14
0
Order By: Relevance
“…The device is based on a design previously published for primary testis cell culture studies. 32 Maintaining a planar surface to allow reliable solvent bonding presents design challenges in the context of injection molding. Areas of varying thickness result in regions of the device cooling and solidifying at different rates and thus variable shrinking arises.…”
Section: Resultsmentioning
confidence: 99%
“…The device is based on a design previously published for primary testis cell culture studies. 32 Maintaining a planar surface to allow reliable solvent bonding presents design challenges in the context of injection molding. Areas of varying thickness result in regions of the device cooling and solidifying at different rates and thus variable shrinking arises.…”
Section: Resultsmentioning
confidence: 99%
“…21 Carney and co-workers cultured primary fetal testis cells in mixed and compartmentalized co-culture to study microenvironmental factors regulating steroid production and organ co-culture assays. 22 However, the method remains underutilized as a microfabrication method compared to other methods. This is largely because of presumed high start-up costs, the need for large equipment and lab space, and the need for unique technical expertise.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Researchers have used micromilling extensively for fabrication of microfluidic devices including Kit-On-A-Lid-Assays (KOALA) in which multiple slides fabricated by micromilling can be combined for fluid delivery, 15 cell capture devices with oil and aqueous interfaces, 16 and devices for microenvironmental studies on primary foetal testis cells. 17 The machinability studies on polymer materials revealed that the elastomers like PDMS (polydimethylsiloxane) are difficult to process using micromilling. 12 PMMA has higher machinability compared to PDMS, and PMMA microfluidic devices have the advantage of having least hydrophobic nature 18 compared to other polymers.…”
Section: Introductionmentioning
confidence: 99%